Knowledge Economies in the Middle East and North Africa : Toward New Development Strategies - Aubert, Jean-Eric; Reiffers, Jean-Louis (Washington, DC: World Bank, 2013)
This book analyzes the development of knowledge-based economies in the Middle East and North Africa (MENA). Its principal messages are: Because of the so-called "knowledge revolution" resulting from the rapid growth in information and communication technologies (ICT), the acceleration of technical change and the intensification of globalization, a new form of economic development is taking shape worldwide. The knowledge revolution presents MENA countries with challenges and opportunities. They need to take advantage of this new source of growth and employment. To date, related investments in education, information infrastructure, research and development (R&D), and innovation have been insufficient or inappropriate in most MENA countries. Moreover, inadequate economic and institutional frameworks prevent these investments from yielding desired results. MENA countries risk falling further behind in the world economy. Urgent action is needed to advance structural reform and to intensify and adapt knowledge-related investments. These messages concur with those of two important recent reports on Arab economies by the United Nations Development Programme (UNDP, 2002) and the World Economic Forum (2003). While there seems to be agreement on what needs to be done in the region, the question of how to achieve the desired results is unfortunately often left unexplored. This is to be the focus of further World Bank conferences.